Ant Colony Optimization Pada Klasifikasi Mangga Gadung Dan Mangga Manalagi - Febri Liantoni; Luky Agus Hermanto (Institut Teknologi Adhi Tama Surabaya)
Examples of types of mango that can be used for food is mango gadung and mango manalagi. In this study taken the topic of the classification of mango gadung and mango manalagi. The process of introduction of mango leaves of gadung and mango manalagi is done based on image edge detection of mango leaf structure. In the process of edge detection is used ant colony optimization (ACO) method that replaces conventional detection. Application of ant colony optimization method successfully optimizes the result of edge detection of a mango leaf bone structure. This is demonstrated by the detection of bony edges of leaf bone structure and more detail than using Roberts or Sobel edge detection. The result of classification test using k-nearest neighbor method got 67,5% accuracy.